PELATIHAN LAPORAN KEUANGAN KEMASAN PRODUK DAN PEMASARAN KEPADA PELAKU USAHA BAKSO IKAN DI DESA WANASALAM LEBAK - Riyanthi Idayu; Efi Tajuroh Afiah; Aris Trismayadi Nurizki; Deni Sunaryo (Jurnal Abdimas Bina Bangsa, 2023)
The activities of business actors processing sea fish in the form of fish balls in Wanasalam Village experience problems including: human resources in managing financial reports, product packaging innovations and marketing processes, so that they affect the sustainability of the business itself, as well as the role of the Wanasalam Village apparatus, still lacking in assisting the development of the fishball business. The purpose of this service is to help improve the skills and abilities of fishball business actors in managing financial reports, innovation and marketing of information technology-based products. Method of implementation: providing training on financial report management, product packaging innovation and marketing strategies both conventionally and online (e-commerce), assistance after training. The results of the training show that fishball business actors in Wanasalam Village, show an increase in managing business management, financial reports, can create attractive product packaging and can implement marketing strategies both conventionally and online (e-commerce), so that an increase in sales volume of fishball products